Rehabilitation of soil salinity and sodicity using diverse amendments and plants: a critical review - Ashenafi Worku Daba (Discover Environment)
Abstract Salt affected soils significantly constrain crop production and soil productivity. Although salt accumulation in soil occurs naturally, human-induced factors such as poor agricultural practices, insufficient drainage systems, as well as inaccurate irrigation water management have accelerated the formation of salt affected soils. The increase in salinity and/or sodicity, coupled with population growth, threatens crop production and soil productivity. According to the FAO/UNESCO soil map, approximately 1030 million hectares of land worldwide are degraded due to excessive salt exposure. Reclaiming these salt-affected soils while improving plant resistances to soil salinity and/or sodicity is critical. Various reclamation and management approaches, including applying different amendments, tolerant genotype cultivation, appropriate agricultural water management, and bioremediation, have effectively addressed salt-affected soils. These strategies, incorporating best practices from many agroecologies, contribute to farmers' socioeconomic well-being in affected areas. This review paper evaluates strategies for enhancing salt-affected soil productivity and the challenges of their adoption.